Assessing a Multidisciplinary Group of Undergraduate Students Applying the Challenge Based Learning Methodology to Learn Mobile Development - Costa, Andrew Diniz da; Coelho, Hendi Lemos; Venieris, Ricardo Almeida; Lucena, Carlos José Pereira de; Carvalho, Gustavo Robichez; Pereira, Marcelo Fernandes (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2020: Anais do XXXIV Simpósio Brasileiro de Engenharia de Software, 2020)
Assessment is an important part of the learning experience, because it helps to clarify what students regard as important, how they spend their time and how they come to see themselves as learners. Besides, assessing students using new learning methodologies, which avoid the idea of teachers as the center of knowledge and students as secondary actors, allow us to understand their advantages and disadvantages. Challenge Based Learning (CBL) is one of these proposals, created with the essential principles of which skills are expected to the 21st century. This paper presents an experience applying an assessment approach during one year to a multidisciplinary group of students, who learned how to develop mobile applications using CBL and came from different universities and courses. The main focus is to allow those students to learn to self-assess them, understand their learning progress on ten technical topics, and share learned lessons from that experience.